Direct microscopy in suppurative keratitis: a report from tertiary level hospital in Nepal - Rai, Pooja Gautam; Chaudhary, Meenu; Sharma, Ananda Kumar; Gautam, Vijay (Nepalese Journal of Ophthalmology, 2017)
Introduction: Infective keratitis is an ocular emergency that requires prompt diagnosis for appropriate management. This study was done todetermine the sensitivity, specificity and predictive values of Gram stain and potassium hydroxide (KOH) wet mount in the diagnosis of suppurative keratitis. Materials and methods: A prospective hospital based study of all patients with clinically diagnosed suppurative keratitis presenting between January 2011 and June 2012 was carried out. Corneal scrapes were taken and subjected to direct microscopy and culture.Results: Corneal scrapings were obtained from 108 eyes with suppurative keratitis. Direct microscopy was positive in 39.2% of cases and organisms were grown in 50.9 % of the cases. Bacteria were responsible in 76.4% and fungi in 23.6%. Of the bacterial isolates, 66.7% was Staphylococcus aureus and of the fungal isolates, 30.7% was Aspergillus species. Sensitivity in vitro showed that Cefazolin, Chloramphenicol and Ofloxacin were most effective against bacteria. Sensitivity of Gram stain in detecting bacteria was 50% (95% CI, 34.43 to 65.56) and specificity was 77.3% (95% CI, 65.0 to86.3) and sensitivity of KOH wet mount in detecting fungi was 53.8% (95% CI, 26.12 to79.6) and specificity was 98.9% (95% CI, 93.44 to 99.9). Positivity of direct smear (65.1%) was found to be higher among eyes with larger ulcers (>2mm) than eyes with smaller ulcers (